Separation membrane as well as preparation method and application thereof

The preparation of seeds with suitable particle size through one-step hydrothermal method and hydrothermal growth is simplified, the preparation process of metal-organic framework separation membrane is solved, the problems of complex processes and high cost in the existing technology are solved, and high gas flux and Selective separation membrane, suitable for gas separation process.

CN119258811AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310821781.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-07
Estimated Expiration
2043-07-06

AI Technical Summary

Technical Problem

The existing metal-organic frame separation membrane preparation process is complex, the cost is high, the membrane layer structure control is difficult, and the gas separation performance is not ideal.

Method used

The one-step hydrothermal method is used to prepare seed crystals with suitable median particle size, and the film is formed by hydrothermal growth, which simplifies the process flow, reduces energy consumption, and improves the controllability of the film layer structure. The separation membrane produced has high gas flow quantity and high selectivity.

Benefits of technology

The high gas flux and selectivity of the separation membrane are achieved, the preparation cost is reduced, the process reliability and separation performance are improved, and it is suitable for gas separation processes such as ethylene/ethane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004323671400000091
    Figure BDA0004323671400000091
  • Figure BDA0004323671400000092
    Figure BDA0004323671400000092
  • Figure BDA0004323671400000141
    Figure BDA0004323671400000141
Patent Text Reader

Abstract

The invention relates to the technical field of gas separation, and discloses a separation membrane and a preparation method and application thereof, the preparation method comprises the following steps: (1) mixing a first metal source, a first organic ligand, a first alkali source, a granularity regulator and a first solvent, and carrying out hydrothermal reaction to obtain a seed crystal; the median particle diameter of the seed crystal is 0.1-8 [mu] m; (2) preparing a dispersion liquid containing the seed crystal; (3) coating the dispersion liquid on the surface of a support body to obtain a separation membrane intermediate; and (4) preparing a membrane synthesis mother solution containing a second metal source, a second organic ligand, a second alkali source and a second solvent, and then carrying out hydrothermal growth on the surface of the separation membrane intermediate for at least one time to form the membrane. The separation membrane prepared by the preparation method has the advantages of high gas flux, high selectivity, low cost, strong reliability and good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas separation, and in particular to a separation membrane and a preparation method and application thereof. Background Art

[0002] Membrane separation technology is a high-efficiency and low-cost separation technology that has been widely used in industrial processes such as water treatment and solvent recovery. In the field of gas separation, polycrystalline separation membranes composed of porous materials such as molecular sieve membranes and metal organic framework membranes have a highly uniform pore structure, which can effectively separate and concentrate gas molecules that preferentially permeate through the molecular sieving effect. However, there are still certain problems in the preparation and performance of existing porous material membranes, including long preparation processes, high energy consumption, and insufficient membrane separation selectivity and gas flux.

[0003] 3,4,5-Trihydroxybenzoate type (also known as gallic acid type or M-Gallate) metal organic framework is a microporous material developed in recent years, with the molecular formula M(C7O5H4)·2H2O. CN112156659A discloses a method for preparing such metal organic framework using ball milling seed method and diffusion method; a research group of Dalian University of Technology reported a method for preparing such metal organic framework using freezing diffusion method (DOI:10.1021 / acsmaterialslett.2c01107). Although the above method can realize the application of such metal organic framework membrane in ethylene / ethane membrane separation process. However, the above-mentioned prior art preparation process is complicated, and ball milling, freezing and other methods are required, which increases additional energy consumption, makes it difficult to control the membrane structure, and makes the membrane performance adjustment inflexible. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of the prior art in that the preparation process of metal organic framework separation membranes is complex, the cost is high, the membrane layer structure is difficult to control, and the gas separation performance is not ideal, and to provide a separation membrane and its preparation method and application. The preparation method has a simple route and strong process controllability. The separation membrane prepared can be effectively used in the separation process of gases such as ethylene / ethane. The separation membrane prepared has high gas flux and high selectivity.

[0005] In order to achieve the above object, the present invention provides a first aspect of a method for preparing a separation membrane, comprising the following steps:

[0006] (1) mixing a first metal source, a first organic ligand, a first alkali source, a particle size regulator and a first solvent, and performing a hydrothermal reaction to obtain seed crystals; the median particle size of the seed crystals is 0.1-8 μm;

[0007] (2) preparing a dispersion containing the seed crystals;

[0008] (3) coating the dispersion on the surface of a support to obtain a separation membrane intermediate;

[0009] (4) preparing a membrane synthesis mother solution containing a second metal source, a second organic ligand, a second alkali source and a second solvent, and then performing at least one hydrothermal growth to form a membrane on the surface of the separation membrane intermediate.

[0010] Preferably, the metal elements in the first metal source include Co and / or Mg; the metal elements in the second metal source include Mg, and optionally Co and / or Ni.

[0011] The second aspect of the present invention provides a separation membrane obtained by the above separation membrane preparation method.

[0012] A third aspect of the present invention provides use of the above separation membrane in gas separation.

[0013] The preparation method of the separation membrane provided by the present invention is to prepare a seed crystal with a suitable median particle size by a one-step hydrothermal method, and then perform hydrothermal growth to form a membrane. The preparation process is simple and controllable, and no additional steps such as ball milling and freezing are required. The separation membrane prepared by the preparation method has high gas flux and high selectivity, low cost, high reliability, and good application prospects. In a preferred case, by optimizing the composition of the metal in the seed crystal and the membrane-forming mother solution, it is beneficial to further improve the separation performance of the separation membrane. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] A first aspect of the present invention provides a method for preparing a separation membrane, comprising the following steps:

[0016] (1) mixing a first metal source, a first organic ligand, a first alkali source, a particle size regulator and a first solvent, and performing a hydrothermal reaction to obtain seed crystals; the median particle size of the seed crystals is 0.1-8 μm;

[0017] (2) preparing a dispersion containing the seed crystals;

[0018] (3) coating the dispersion on the surface of a support to obtain a separation membrane intermediate;

[0019] (4) preparing a membrane synthesis mother solution containing a second metal source, a second organic ligand, a second alkali source and a second solvent, and then performing at least one hydrothermal growth to form a membrane on the surface of the separation membrane intermediate.

[0020] In the present invention, a seed crystal with a suitable median particle size is prepared by a one-step method, and then a separation membrane intermediate surface coated with the seed crystal is hydrothermally grown to form a film, which can reduce the difficulty of metal organic framework film formation and facilitate the control of the membrane layer structure of the separation membrane. The separation membrane prepared has high gas flux and high selectivity.

[0021] Metal organic framework is a microporous material developed in recent years. Due to the difficulty of metal organic framework film formation, the preparation process of metal organic framework membrane in the prior art is relatively complicated, usually using ball milling seed with diffusion method or freezing diffusion complex process, the process control is difficult, the cost is high, and the membrane performance adjustment is not flexible. The inventors of the present invention found in the study that by controlling the median particle size of the seed within an appropriate range, it is conducive to forming a dense and continuous metal organic framework membrane layer, and the separation performance of the obtained separation membrane is good.

[0022] The median particle size of the metal organic framework seeds obtained by conventional hydrothermal crystallization in the prior art is relatively large, generally above 25 μm. In the present invention, by introducing a particle size regulator to control the hydrothermal reaction, the median particle size of the obtained seeds is 0.1-8 μm. If the particle size of the seeds is too large, it may lead to difficulties in the interaction and symbiosis between crystals, increase defects, reduce selectivity, increase membrane thickness, and reduce membrane flux; if the particle size is too small, the seeds may enter the pores of the support layer, thereby affecting the membrane flux.

[0023] According to some preferred embodiments of the present invention, the median particle size of the seed is 0.2-1.2 μm, preferably 0.4-0.9 μm. In the above preferred case, controlling the seed particle size within the above suitable range is conducive to the subsequent hydrothermal growth of the metal organic framework film, and is conducive to the flexible adjustment of the film layer composition, which is conducive to further improving the density of the subsequent hydrothermal growth film and improving the separation performance.

[0024] In the present invention, the term "median particle size" refers to the particle size corresponding to when the cumulative particle size distribution percentage of a seed crystal sample reaches 50%, which represents the average particle size in the present invention.

[0025] In the present invention, the median particle size of the seed crystal is obtained by testing with a dynamic light scattering laser particle size analyzer.

[0026] The present invention has a wide range of selection for the specific type of the particle size regulator, as long as the median particle size of the seed crystal obtained by the hydrothermal reaction can be adjusted to be within the above range. Preferably, the particle size regulator is selected from at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, octadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, sodium lauryl sulfate, dodecanoic acid, polyvinylpyrrolidone, benzoic acid, formic acid, acetic acid and triethylamine, and is more preferably cetyltrimethylammonium bromide.

[0027] In the present invention, there is no special requirement for the mixing order of the first metal source, the first organic ligand, the first alkali source, the first solvent and the particle size regulator, and the conventional operation method in the art can be adopted. Preferably, the first alkali source and the first solvent are first mixed, and then the first organic ligand is added, followed by the first metal source, and finally the particle size regulator is added. The above preferred embodiment is conducive to the full dissolution of each component to form a homogeneous system or a uniformly dispersed system.

[0028] According to some preferred embodiments of the present invention, the molar ratio of the first metal source, the first organic ligand, the first alkali source, the particle size regulator and the solvent, calculated as metal elements, satisfies the following: n(first metal source):n(first organic ligand):n(first alkali source):n(particle size regulator):n(first solvent)=1:(1-5):(1-6):(0.01-1.8):(100-500), preferably 1:(1.8-3.5):(2-4):(0.14-0.9):(200-400).

[0029] In the present invention, the “first” and “second” in the “first metal source” and “second metal source”, “first organic ligand” and “second organic ligand”, “first alkali source” and “second alkali source”, “first solvent” and “second solvent” are only used to distinguish the raw materials in different steps and do not play a limitative role on the present invention.

[0030] According to some preferred embodiments of the present invention, the metal elements in the first metal source and the second metal source are each independently selected from at least one of Co, Mg and Ni.

[0031] In the present invention, the metal elements in the first metal source and the second metal source may be the same or different.

[0032] According to some preferred embodiments of the present invention, the metal elements in the first metal source include Co and / or Mg; preferably, the metal elements in the first metal source include Co, and optionally Mg.

[0033] Preferably, the metal elements of the first metal source include Co and Mg, and the molar ratio of Co to Mg is 1:0.05-20, preferably 1:0.1-10.

[0034] According to some preferred embodiments of the present invention, the metal element in the second metal source is selected from at least one of Co, Mg and Ni; preferably, the metal element in the second metal source includes Mg, and optionally Co and / or Ni.

[0035] Preferably, the metal elements of the second metal source include Mg, and Co and / or Ni, and the total molar ratio of Mg element to Co and / or Ni element is 1:0.05-20, preferably 1:0.1-10, and more preferably 1:0.2-0.5. In the above preferred case, it is beneficial to further improve the gas flux and selectivity of the separation membrane.

[0036] According to a particularly preferred embodiment of the present invention, the metal element in the first metal source includes Co, and the metal element in the second metal source includes Mg, and Co and / or Ni. By adopting the above preferred embodiment, the separation membrane prepared can take into account both high gas flux and high selectivity.

[0037] According to some preferred embodiments of the present invention, the first metal source and the second metal source are soluble salts that can provide the above metal elements, such as at least one of chloride, nitrate and sulfate. The first metal source and the second metal source may also contain crystal water, which is well known to those skilled in the art.

[0038] According to some preferred embodiments of the present invention, the first organic ligand and the second organic ligand are 3,4,5-trihydroxybenzoic acid, also known as gallic acid. The gallic acid may also include water of crystallization. In the above case, the chemical composition of the seed crystal obtained in step (1) or the hydrothermal growth film in step (4) can be independently expressed as M(C7O5H4)·2H2O, wherein M is selected from at least one of Co, Mg and Ni, and it is further preferred that M corresponds to the metal type in the above preferred embodiment.

[0039] According to some preferred embodiments of the present invention, the first alkali source and the second alkali source are each independently selected from at least one of potassium hydroxide, sodium hydroxide and lithium hydroxide, preferably potassium hydroxide. The first alkali source and the second alkali source can be provided in the form of an aqueous solution of alkali.

[0040] According to some preferred embodiments of the present invention, the first solvent and the second solvent are each independently selected from at least one of water, methanol, ethanol, N,N-dimethylformamide and N,N-dimethylacetamide, preferably water.

[0041] According to some preferred embodiments of the present invention, in step (1), the conditions of the hydrothermal reaction include: a temperature of 50-200° C., preferably 70-140° C.; and a time of 1-168 hours, preferably 8-48 hours. Under the above preferred reaction conditions, it is beneficial to shorten the preparation cycle and reduce energy consumption while generating qualified seed crystals that meet the particle size requirements.

[0042] In the present invention, preferably, the method further comprises: subjecting the product of the hydrothermal reaction to solid-liquid separation, washing and drying to obtain the seed crystal. The present invention has no particular limitation on the specific manner and conditions of the solid-liquid separation, washing and drying, and the conventional operation methods in the art can be used for the above-mentioned process.

[0043] According to the present invention, in step (2), the seed crystals are dispersed in a solvent to obtain a dispersion containing the seed crystals, and then the coating in step (3) is performed. The solvent is preferably water.

[0044] According to some preferred embodiments of the present invention, in step (2), the mass concentration of the dispersion is 0.01-5%, preferably 0.1-1.5%, and more preferably 0.2-0.5%.

[0045] In the present invention, there is no particular limitation on the coating method in step (3), and the coating can be carried out using conventional methods and operating conditions in the art. Preferably, the coating method is selected from a room temperature dip coating method, a hot dip coating method or a vacuum dip coating method, preferably a room temperature dip coating method. The room temperature dip coating method can be carried out at room temperature and pressure.

[0046] The present invention has no particular limitation on the coating thickness and coating amount of the seed crystals. Preferably, a single-layer dense coating is adopted, and the excess seed crystals can be gently wiped off after coating so that the coating thickness of the seed crystals is substantially consistent with the median particle size of the seed crystals.

[0047] In the present invention, there is no particular limitation on the number of times the seed crystal is coated, and multiple coatings may be performed, which is well known to those skilled in the art. Preferably, the number of coatings is 1-20 times, preferably 2-10 times, and more preferably 3-6 times, and a drying process is preferably included between any two coatings. Preferably, the temperature of the drying process is 20-150° C., preferably 40-100° C.

[0048] The seeds in the seed dispersion of the present invention are any seeds that meet the particle size range mentioned above. Seeds with a single particle size distribution may be used alone, seeds with different single particle size distributions may be used in multiple coating processes, or seeds with multiple particle size distributions may be directly mixed.

[0049] In the present invention, the support may be an inorganic porous support, for example, may be at least one of aluminum oxide, silicon oxide, titanium oxide, chromium oxide, iron oxide, zirconium oxide, yttrium oxide, copper oxide, phosphorus oxide, silicon carbide and elemental carbon.

[0050] The present invention has no particular limitation on the shape of the support body. For example, the support body is in the form of a flat plate, a tube or a hollow fiber, and is preferably a tube support body.

[0051] The size and specification of the support in the present invention are not particularly limited, and a support having a conventional length, thickness, diameter, pore size, and porosity in the art can be used. Preferably, the porosity of the support is 20-70%, preferably 30-50%. In the above preferred case, it is beneficial to reduce the mass transfer resistance of the support while having a certain mechanical strength.

[0052] According to some preferred embodiments of the present invention, the pore size of the support is no more than 2 times the median particle size of the seed crystal, and preferably, the pore size of the support is 0.05-1.8 μm. In the above preferred case, it is beneficial to obtain a higher gas flux while ensuring the density of the membrane. The reason may be that in the above case, the seed crystal can avoid entering the support pore through the bridging effect; if the pore size of the support is too large, the probability of the seed crystal entering the support pore may be greatly increased, resulting in pore blockage, thereby affecting the gas flux.

[0053] According to some preferred embodiments of the present invention, the molar ratio of the second metal source, the second organic ligand, the second alkali source and the second solvent in the membrane synthesis mother liquor, calculated as metal elements, satisfies the following: n(second metal source):n(second organic ligand):n(second alkali source):n(second solvent)=1:(1-5):(1-8):(200-20000), preferably 1:(1.8-2.2):(2-4):(800-4000).

[0054] The present invention has no particular limitation on the specific operation and conditions of the hydrothermal growth film, and can be carried out by conventional methods in the art, as long as the uniform film formation of the metal organic framework film is satisfied. Preferably, in step (4), the hydrothermal growth film comprises: immersing the separation membrane intermediate in the membrane synthesis mother solution, performing a second hydrothermal reaction, washing and drying.

[0055] Preferably, the conditions of the second hydrothermal reaction include: temperature of 50-180°C, preferably 60-120°C; time of 2-168h, preferably 16-72h.

[0056] According to some preferred embodiments of the present invention, the reaction temperature of the second hydrothermal reaction is not higher than the reaction temperature of the hydrothermal reaction in step (1), and / or the reaction time of the second hydrothermal reaction is not less than the reaction time of the hydrothermal reaction in step (1). Preferably, the reaction temperature of the second hydrothermal reaction is lower than the reaction temperature of the hydrothermal reaction in step (1), and the reaction time of the second hydrothermal reaction is greater than the reaction time of the hydrothermal reaction in step (1).

[0057] The above preferred embodiment is conducive to improving the separation effect of the separation membrane. The reason may be that under the above conditions, the formation of metal organic framework particles in the bulk phase can be reduced, so that nutrients can be used as much as possible for metal organic framework film formation, and a longer reaction time is conducive to improving the density of the membrane layer, so that the separation membrane has a suitable gas flux and excellent selectivity.

[0058] Preferably, the thickness of the membrane layer obtained by hydrothermal growth is 50nm-50μm, preferably 0.5-20μm, and more preferably 10-15μm. In the case of the above preferred membrane layer thickness, it is beneficial to further improve the separation performance of the separation membrane.

[0059] In the present invention, the film thickness is measured by scanning electron microscopy. The film thickness is measured in three different film regions and the average value is taken.

[0060] Preferably, the number of times of hydrothermal growth to form a membrane is 1-20 times, preferably 1-4 times, so as to meet the thickness requirement of the above separation membrane.

[0061] The second aspect of the present invention provides a separation membrane obtained by the above preparation method.

[0062] According to the present invention, the separation membrane comprises a support body and a metal organic framework membrane layer composited on the surface of the support body.

[0063] Preferably, the chemical composition of the metal organic framework film layer can be expressed as M(C7O5H4)·2H2O, wherein M is selected from at least one of Co, Mg and Ni.

[0064] A third aspect of the present invention provides use of the above separation membrane in gas separation.

[0065] The present invention has a wide selection range for the types of gases, and the metal organic framework membrane is suitable for separation of any gas system in the art. Preferably, the gas separation includes ethane-ethylene separation, propylene-propane separation or hydrogen-methane separation.

[0066] The present invention will be described in detail below through examples.

[0067] Unless otherwise specified, the raw materials used in the following examples and comparative examples are commercially available.

[0068] In the present invention, the gas permeability of the metal organic framework membrane is measured by a membrane gas permeation device, and the specific operating conditions include:

[0069] Using the differential pressure method, the feed side of the membrane is a single gas with a certain pressure, and the permeate side is another constant pressure, usually normal pressure. By measuring the gas volume flow rate when the gas stably permeates the membrane, the permeability of the single gas on the membrane is calculated, and the formula is as follows:

[0070]

[0071] Where GTR is the gas transmission rate, the unit is mol / (m 2 ·s·Pa), which represents the number of moles of gas that permeate the unit membrane area per unit time per unit pressure difference; Q is the volume flow rate of gas permeating the membrane, in units of m 3 / s; R is the gas constant, its value is 8.314m 3 ·Pa / (K·mol); T is the system temperature, its unit is K; A is the effective membrane area, its unit is m 2 ;P feed and P perm They are feed pressure and permeate pressure respectively, and their unit is Pa.

[0072] Comparing the permeability of two arbitrary gases, we can obtain the ideal gas selectivity of the membrane for this pair of gases. The formula is as follows:

[0073]

[0074] Where S is the ideal selectivity of the membrane to a pair of gases, with a dimension of 1; GTR1 and GTR2 are the gas permeabilities of gas 1 and gas 2 to the membrane, respectively.

[0075] The median particle size of the seed crystals was measured by a dynamic light scattering laser particle size analyzer.

[0076] Example 1

[0077] (1) Seed crystal synthesis: The raw materials are cobalt chloride hexahydrate (2.618 g, 0.011 mol), gallic acid monohydrate (4.703 g, 0.025 mol), KOH (2.05 g, purity of 85 wt%, 0.031 mol), cetyltrimethylammonium bromide (CTAB) (1.749 g, 0.0048 mol), and deionized water (60 mL, 3.333 mol). Deionized water, KOH, gallic acid monohydrate, cobalt chloride hexahydrate, and CTAB are slowly added in this order while stirring. The next reagent is added after the added reagent is completely dissolved. The mixture is sealed in a polytetrafluoroethylene-lined hydrothermal reactor and subjected to static hydrothermal synthesis at 110° C. for 10 h. The mixture is washed with water and ethanol and dried at 80° C. for 8 h to obtain seed crystals. The median particle size of the seed crystals is obtained by dynamic light scattering laser particle size analyzer, as shown in Table 1.

[0078] (2) Seed coating: The above-mentioned seed crystals are dispersed in deionized water to prepare a seed crystal dispersion with a concentration of 0.2wt%. Seal both ends of an alumina ceramic tube with a total length of 6.5cm, a surface pore size of 0.5μm, and an outer diameter of 12mm, fix it on a vertical immersion and pulling machine, immerse it in the seed crystal dispersion at a speed of 8000μm / s, hold it for 1min, and pull it at a speed of 1000μm / s. The coating process is repeated 4 times, each time drying at room temperature for 1h and 80℃ for 30min. After the last coating, the drying time at 80℃ is increased to 12h, and a single-layer coated alumina ceramic tube is prepared.

[0079] (3) Hydrothermal growth of membrane: Prepare a membrane synthesis mother solution containing magnesium chloride hexahydrate (2.8mmol), gallic acid monohydrate (1.054g, 5.6mmol), KOH (0.462g, purity of 85wt%, 7mmol), and deionized water (140mL, 7.77mol), and add deionized water, KOH, gallic acid monohydrate, magnesium chloride hexahydrate, cobalt chloride hexahydrate, and nickel chloride hexahydrate in the order of addition, and add slowly while stirring to ensure that the added reagents are completely dissolved before adding the next reagent. Subsequently, seal both ends of the coated alumina ceramic tube, insert a polytetrafluoroethylene liner, and slowly pour the above membrane synthesis mother solution. Subsequently, place the polytetrafluoroethylene liner in a stainless steel hydrothermal reactor, perform hydrothermal synthesis at 80°C for 24h, wash with water and ethanol, and dry at 80°C for 8h to prepare a metal organic framework separation membrane. The prepared separation membrane comprises a support layer and a metal organic skeleton membrane composited on the support layer, and the thickness of the metal organic skeleton membrane is 14 μm.

[0080] The gas separation performance of the separation membrane was evaluated using a cross-flow membrane evaluation device.

[0081] The gauge pressure on the feed side is 0.3 MPa, the permeate side is at normal pressure, and the test temperature is 25°C. The measured permeability (GTR) of C2H4 is 1.66×10 -8 mol / (m 2 ·s·Pa), the transmittance (GTR) of C2H6 is 2.1×10 -9 mol / (m 2 ·s·Pa), the ideal selectivity of C2H4 / C2H6 is 7.90.

[0082] Example 2

[0083] (1) Seed crystal synthesis: The raw materials are cobalt chloride hexahydrate (2.618 g, 0.011 mol), gallic acid monohydrate (4.703 g, 0.025 mol), KOH (2.05 g, purity of 85 wt%, 0.031 mol), cetyltrimethylammonium bromide (CTAB) (1.312 g, 0.0036 mol), and deionized water (60 mL, 3.333 mol). Deionized water, KOH, gallic acid monohydrate, cobalt chloride hexahydrate, and CTAB are slowly added in this order while stirring. The next reagent is added after the added reagent is completely dissolved. The mixture is sealed in a polytetrafluoroethylene-lined hydrothermal reactor and subjected to static hydrothermal synthesis at 120° C. for 8 h. The mixture is washed with water and ethanol and dried at 80° C. for 8 h to obtain seed crystals. The median particle size of the seed crystals is obtained by dynamic light scattering laser particle size analyzer, as shown in Table 1.

[0084] (2) Seed coating: The above-mentioned seed crystals are dispersed in deionized water to prepare a seed crystal dispersion with a concentration of 0.2wt%. Seal both ends of an alumina ceramic tube with a total length of 6.5cm, a surface pore size of 0.5μm, and an outer diameter of 12mm, fix it on a vertical immersion and pulling machine, immerse it in the seed crystal dispersion at a speed of 8000μm / s, hold it for 1min, and pull it at a speed of 1000μm / s. The coating process is repeated 4 times, each time drying at room temperature for 1h and 80℃ for 30min. After the last coating, the drying time at 80℃ is increased to 12h, and finally a single-layer coated alumina ceramic tube is prepared.

[0085] (3) Hydrothermal growth of membrane: Prepare a membrane synthesis mother solution containing magnesium chloride hexahydrate (0.455g, 2.24mmol), cobalt chloride hexahydrate (0.133g, 0.56mmol), gallic acid monohydrate (1.129g, 6.0mmol), KOH (0.462g, purity of 85wt%, 7mmol), and deionized water (160mL, 8.88mol), and add deionized water, KOH, gallic acid monohydrate, magnesium chloride hexahydrate, and cobalt chloride hexahydrate in the order of adding, slowly adding while stirring, and ensure that the added reagents are completely dissolved before adding the next reagent. Subsequently, seal both ends of the coated alumina ceramic tube, insert a polytetrafluoroethylene liner, and slowly pour the above membrane synthesis mother solution. Subsequently, place the polytetrafluoroethylene liner in a stainless steel hydrothermal reactor, perform hydrothermal synthesis at 120°C for 24h, wash with water and ethanol, and dry at 80°C for 8h to prepare a metal organic framework separation membrane. The prepared separation membrane comprises a support layer and a metal organic skeleton membrane composited on the support layer, and the thickness of the metal organic skeleton membrane is 15 μm.

[0086] The composition of the prepared separation membrane is shown in Table 1.

[0087] The gas separation performance of the separation membrane was evaluated using the method of Example 1. The results are shown in Table 1.

[0088] Example 3

[0089] (1) Seed crystal synthesis: The raw materials are cobalt chloride hexahydrate (1.904 g, 0.008 mol), gallic acid monohydrate (5.267 g, 0.028 mol), KOH (1.918 g, purity of 85 wt%, 0.029 mol), cetyltrimethylammonium bromide (CTAB) (2.187 g, 0.006 mol), and deionized water (60 mL, 3.333 mol). Deionized water, KOH, gallic acid monohydrate, cobalt chloride hexahydrate, and CTAB are slowly added in this order while stirring. The next reagent is added after the added reagent is completely dissolved. The mixture is sealed in a polytetrafluoroethylene-lined hydrothermal reactor and subjected to static hydrothermal synthesis at 120° C. for 16 h. The mixture is washed with water and ethanol and dried at 80° C. for 8 h to obtain seed crystals. The median particle size of the seed crystals is obtained by dynamic light scattering laser particle size analyzer, as shown in Table 1.

[0090] (2) Seed coating: The above-mentioned seed crystals are dispersed in deionized water to prepare a seed crystal dispersion with a concentration of 0.2wt%. Seal both ends of an alumina ceramic tube with a total length of 6.5cm, a surface pore size of 0.5μm, and an outer diameter of 12mm, fix it on a vertical immersion and pulling machine, immerse it in the seed crystal dispersion at a speed of 8000μm / s, hold it for 1min, and pull it at a speed of 1000μm / s. The coating process is repeated 4 times, each time drying at room temperature for 1h and 80℃ for 30min. After the last coating, the drying time at 80℃ is increased to 12h, and finally a single-layer coated alumina ceramic tube is prepared.

[0091] (3) Hydrothermal growth of membrane: Prepare a membrane synthesis mother solution containing magnesium chloride hexahydrate (0.398 g, 1.96 mmol), cobalt chloride hexahydrate (0.133 g, 0.56 mmol), nickel chloride hexahydrate (0.067 g, 0.28 mmol), gallic acid monohydrate (1.318 g, 7.0 mmol), KOH (0.594 g, purity of 85 wt%, 9 mmol), and deionized water (140 mL, 7.77 mol), and add deionized water, KOH, gallic acid monohydrate, magnesium chloride hexahydrate, cobalt chloride hexahydrate, and nickel chloride hexahydrate in this order, slowly adding while stirring to ensure that the added reagents are completely dissolved before adding the next reagent. Subsequently, seal both ends of the crystal-coated alumina ceramic tube, insert a polytetrafluoroethylene liner, and slowly pour the above membrane synthesis mother solution. Then, the polytetrafluoroethylene liner was placed in a stainless steel hydrothermal reactor, hydrothermally synthesized at 120°C for 36 hours, washed with water and ethanol, and dried at 80°C for 8 hours to prepare a metal organic skeleton separation membrane. The prepared separation membrane includes a support layer and a metal organic skeleton membrane composited on the support layer, and the thickness of the metal organic skeleton membrane is 14.5 μm.

[0092] The composition of the prepared separation membrane is shown in Table 1.

[0093] The gas separation performance of the separation membrane was evaluated using the method of Example 1. The results are shown in Table 1.

[0094] Example 4

[0095] The method of Example 1 is followed, except that in step (1), benzoic acid is used in an equal molar amount to replace CTAB; the median particle size of the seed crystal is measured by a dynamic light scattering laser particle size analyzer, as shown in Table 1. The composition of the membrane synthesis mother solution in step (3) includes: cobalt chloride hexahydrate (0.666 g, 2.8 mmol), gallic acid monohydrate (1.054 g, 5.6 mmol), KOH (0.462 g, purity of 85 wt%, 7 mmol), and deionized water (140 mL, 7.77 mol). The composition of the prepared separation membrane is shown in Table 1.

[0096] The gas separation performance of the separation membrane was evaluated using the method of Example 1. The results are shown in Table 1.

[0097] Example 5

[0098] The method of Example 1 was followed, except that CTAB was replaced with an equal molar amount of dodecanoic acid. The median particle size of the obtained seed crystals and the composition of the separation membrane are shown in Table 1.

[0099] The gas separation performance of the separation membrane was evaluated using the method of Example 1. The results are shown in Table 1.

[0100] Example 6

[0101] The method of Example 1 is followed, except that magnesium chloride hexahydrate (0.559 g, 2.75 mmol) and cobalt chloride hexahydrate (1.963 g, 8.25 mmol) are used in place of magnesium chloride hexahydrate in the seed crystal synthesis mother liquor of step (1), so that the molar ratio is n(Mg):n(Co)=1:3. The median particle size of the seed crystal is obtained by dynamic light scattering laser particle size analyzer test, as shown in Table 1. The composition of the prepared separation membrane is shown in Table 1.

[0102] The gas separation performance of the separation membrane was evaluated using the method of Example 1. The results are shown in Table 1.

[0103] Example 7

[0104] The method of Example 2 is followed, except that the total molar amount of the second metal source remains unchanged, wherein the molar ratio of n(Mg):n(Co) is 1:30, and the composition of the prepared separation membrane is shown in Table 1.

[0105] The gas separation performance of the separation membrane was evaluated using the method of Example 1. The results are shown in Table 1.

[0106] Comparative Example 1

[0107] The method of Example 4 was followed, except that a particle size regulator was not introduced in step (1). The median particle size of the seed crystals was obtained by dynamic light scattering laser particle size analyzer, as shown in Table 1. The composition of the prepared separation membrane is shown in Table 1.

[0108] The gas separation performance of the separation membrane was evaluated using a cross-flow membrane evaluation device.

[0109] The gauge pressure on the feed side was 0.1 MPa, the permeate side was atmospheric pressure, and the test temperature was 25°C. The measured permeability (GTR) of C2H4 was 5.20×10 -8 mol / (m 2 ·s·Pa), the transmittance (GTR) of C2H6 is 5.03×10 -8 mol / (m 2·s·Pa), the ideal selectivity of C2H4 / C2H6 is 1.03. Since the seed particles are too large, it is difficult to form a dense membrane layer, resulting in excessive membrane flux, greatly reduced selectivity, and poor separation performance.

[0110] Table 1

[0111]

[0112] From the results in Table 1, it can be seen that in the embodiment of the present invention, a seed crystal with a suitable median particle size is prepared by a one-step hydrothermal method, and then hydrothermally grown into a membrane, and the obtained separation membrane can take into account both high ethylene permeability and ethylene / ethane selectivity, and has good separation performance. From the comparison between Example 4 and Comparative Example 1, it can be seen that when the median particle size of the seed crystal is too large, the membrane flux is too large and the selectivity is greatly reduced. This is because the seed crystal particle size is too large, it is difficult to form a dense membrane layer through hydrothermal growth, and the separation performance is poor.

[0113] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a separation membrane, characterized in that: The following steps are involved: (1) mixing a first metal source, a first organic ligand, a first alkali source, a particle size regulator and a first solvent, and performing a hydrothermal reaction to obtain seed crystals; the median particle size of the seed crystals is 0.1-8 μm; (2) preparing a dispersion containing the seed crystals; (3) coating the dispersion on the surface of a support to obtain a separation membrane intermediate; (4) preparing a membrane synthesis mother solution containing a second metal source, a second organic ligand, a second alkali source and a second solvent, and then performing at least one hydrothermal growth to form a membrane on the surface of the separation membrane intermediate.

2. The preparation method according to claim 1, wherein The median particle size of the seed crystals is 0.2-1.2 μm, preferably 0.4-0.9 μm.

3. The preparation method according to claim 1 or 2, wherein The particle size regulator is at least one selected from the group consisting of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, sodium lauryl sulfate, dodecanoic acid, polyvinylpyrrolidone, benzoic acid, formic acid, acetic acid and triethylamine, preferably hexadecyltrimethylammonium bromide; Preferably, the molar ratio of the first metal source, the first organic ligand, the first alkali source, the particle size regulator and the first solvent, calculated as metal elements, satisfies the following: n(first metal source):n(first organic ligand):n(first alkali source):n(particle size regulator):n(first solvent)=1:(1-5):(1-6):(0.01-1.8):(100-500), preferably 1:(1.8-3.5):(2-4):(0.14-0.9):(200-400).

4. The preparation method according to any one of claims 1 to 3, wherein The metal elements in the first metal source and the second metal source are each independently selected from at least one of Co, Mg and Ni; Preferably, the metal elements in the first metal source include Co and / or Mg, preferably Co; Preferably, the metal element in the second metal source is selected from at least one of Co, Mg and Ni; preferably, the metal element in the second metal source includes Mg, and optionally Co and / or Ni; Preferably, the metal elements of the second metal source include Mg, and Co and / or Ni, and the total molar ratio of Mg element to Co and / or Ni element is 1:0.05-20, preferably 1:0.1-10.

5. The preparation method according to any one of claims 1 to 4, wherein: The first organic ligand and the second organic ligand are 3,4,5-trihydroxybenzoic acid; Preferably, the first alkali source and the second alkali source are each independently selected from at least one of potassium hydroxide, sodium hydroxide and lithium hydroxide.

6. The preparation method according to any one of claims 1 to 5, wherein: In step (1), the conditions of the hydrothermal reaction include: temperature of 50-200° C., preferably 70-140° C.; time of 1-168 h, preferably 8-48 h.

7. The preparation method according to any one of claims 1 to 6, wherein: In step (2), the mass concentration of the dispersion is 0.01-5%, preferably 0.1-1.5%, and more preferably 0.2-0.5%; Preferably, the coating method is selected from room temperature dip coating, hot dip coating or vacuum dip coating, preferably room temperature dip coating.

8. The preparation method according to any one of claims 1 to 7, wherein: The molar ratio of the second metal source, the second organic ligand, the second alkali source and the second solvent in the membrane synthesis mother liquid, calculated as metal elements, satisfies the following: n (second metal source): n (second organic ligand): n (second alkali source): n (second solvent) = 1: (1-5): (1-8): (200-20000), preferably 1: (1.8-2.2): (2-4): (800-4000).

9. The preparation method according to any one of claims 1 to 8, wherein: In step (4), the hydrothermal growth of the membrane comprises: immersing the separation membrane intermediate in the membrane synthesis mother solution, performing a second hydrothermal reaction, washing and drying; Preferably, the conditions of the second hydrothermal reaction include: temperature of 50-180°C, preferably 60-120°C; time of 2-168h, preferably 16-72h; Preferably, the reaction temperature of the second hydrothermal reaction is not higher than the reaction temperature of the hydrothermal reaction in step (1), and / or the reaction time of the second hydrothermal reaction is not less than the reaction time of the hydrothermal reaction in step (1); Preferably, the thickness of the film layer obtained by the hydrothermal growth is 50 nm-50 μm, preferably 0.5-20 μm, and more preferably 10-15 μm.

10. The separation membrane obtained by the preparation method according to any one of claims 1 to 9.

11. Use of the separation membrane according to claim 10 in gas separation; Preferably, the gas separation comprises ethane-ethylene separation, propylene-propane separation or hydrogen-methane separation.

Citation Information

Patent Citations

  • M-gallate metal organic framework membrane as well as preparation method and application thereof

    CN112156659A

  • Method for preparing metal organic frame supported film

    CN101912737A

  • Preparation method and application of hierarchical porous molecular sieve membrane

    CN106378013A

  • Method for preparing metal-organic framework UiO-66 series membranes and separating methanol / methyl tert-butyl ether mixture

    CN106492651A

  • Method for controlling particle size of TS-1 molecular sieve crystal, and method for preparing small-grain TS-1 molecular sieve

    CN111115652A